The clinical application of genome-wide sequencing for monogenic diseases in Canada: Position Statement of the Canadian College of Medical Geneticists. Issue 7 (7th May 2015) - Boycott, Kym; Hartley, Taila; Adam, Shelin; Bernier, Francois; Chong, Karen; Fernandez, Bridget A; Friedman, Jan M; Geraghty, Michael T; Hume, Stacey; Knoppers, Bartha M; Laberge, Anne-Marie; Majewski, Jacek; et al.
Abstract : Purpose and scope: The aim of this Position Statement is to provide recommendations for Canadian medical geneticists, clinical laboratory geneticists, genetic counsellors and other physicians regarding the use of genome-wide sequencing of germline DNA in the context of clinical genetic diagnosis. This statement has been developed to facilitate the clinical translation and development of best practices for clinical genome-wide sequencing for genetic diagnosis of monogenic diseases in Canada; it does not address the clinical application of this technology in other fields such as molecular investigation of cancer or for population screening of healthy individuals. Methods of statement development: Two multidisciplinary groups consisting of medical geneticists, clinical laboratory geneticists, genetic counsellors, ethicists, lawyers and genetic researchers were assembled to review existing literature and guidelines on genome-wide sequencing for clinical genetic diagnosis in the context of monogenic diseases, and to make recommendations relevant to the Canadian context. The statement was circulated for comment to the Canadian College of Medical Geneticists (CCMG) membership-at-large and, following incorporation of feedback, approved by the CCMG Board of Directors. The CCMG is a Canadian organisation responsible for certifying medical geneticists and clinical laboratory geneticists, and for establishing professional and ethical standards for clinical genetics services in Canada. Results and conclusions: Recommendations include (1) clinical genome-wide sequencing is an appropriate approach in the diagnostic assessment of a patient for whom there is suspicion of a significant monogenic disease that is associated with a high degree of genetic heterogeneity, or where specific genetic tests have failed to provide a diagnosis; (2) until the benefits of reporting incidental findings are established, we do not endorse the intentional clinical analysis of disease-associated genes other than those linked to the primary indication; and (3) clinicians should provide genetic counselling and obtain informed consent prior to undertaking clinical genome-wide sequencing. Counselling should include discussion of the limitations of testing, likelihood and implications of diagnosis and incidental findings, and the potential need for further analysis to facilitate clinical interpretation, including studies performed in a research setting. These recommendations will be routinely re-evaluated as knowledge of diagnostic and clinical utility of clinical genome-wide sequencing improves. While the document was developed to direct practice in Canada, the applicability of the statement is broader and will be of interest to clinicians and health jurisdictions internationally.